PENGEMBANGAN MEDIA E-AMBO (E-BOOK AMAZING BODY) UNTUK PEMBELAJARAN BAHASA INGGRIS SISWA SD KELAS V - Oktavia, Elda; Qurrotu Inayatil Maula (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This development research aimed to produce E-AMBO (E-Book Amazing Body) media for English learning among fifth-grade elementary school students and to determine its validity, effectiveness, and attractiveness. The research was motivated by the need for innovative learning media that could improve students’ vocabulary mastery and learning engagement in English lessons. This study employed the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research subjects were 25 fifth-grade students of SDN Jalmak 1, Pamekasan Regency.The results showed that the developed E-AMBO media was highly valid, with validation scores of 95% from media experts, 97.5% from learning design experts, 98% from material experts, and 85% from language experts. The media was also highly effective, as indicated by teacher activity observations (95.8%), student activity observations (85.4%), and learning media implementation observations (85%). In addition, students achieved a classical learning completeness score of 85.7%, which met the predetermined mastery criteria. Furthermore, the E-AMBO media was categorized as highly attractive based on the teacher response questionnaire result of 97.5% and the student response questionnaire result of 88.3%. Therefore, it can be concluded that the E-AMBO media (E-Book Amazing Body) is valid, effective, and attractive for use in English learning for fifth-grade elementary school students.